Evaluation of drill and blast excavation quality for a tunnel. Issue 4 (October 2021) - Wang, Jianxiu; Wu, Fan; Zhou, Xiaobo; Hu, Lisheng
Abstract: Under complex engineering-geological conditions, the drill and blast method is often adopted to excavate a tunnel. The smooth blasting method (SBM) is used to control excavation quality. However, over break and under break often occur and even cause engineering disasters. Therefore, it is imperative to ascertain evaluation methods of the SBM quality for tunnel engineering. Based on in-site measurement and monitoring, a drill and blast quality evaluation system was developed. Nine indicators were selected in the system. For example, the evaluation method was used to evaluate and direct the excavation with a railway tunnel.